TINGKAT PARTISIPASI STAKEHOLDERS DALAM PENINGKATAN INDEKS DESA MANDIRI - Junaidi, Junaidi; Edy Agustinus; Giska Hediyanti (JURNAL BORNEO AKCAYA, 2019)
Specifically, this paper aims to analyze the level of stakeholder participation in increasing the Independent Village Index (IDM) in Sambas Regency. The research, which was conducted between August 2019-December 2019, took place in 4 (four) villages which are included in the priority of increasing the village independence status in Sambas Regency in 2020. The villages in question are: Sempalai Sebedang Village, Sebawi District; Durian Village, Sambas District; Sumber Harapan Village, Sambas District; and Sebubus Village, Paloh District. The results of this quantitative research show that: first, the level of community participation is generally classified as "strong" and "very strong". However, the community's willingness to provide material in order to support village development falls into the "adequate" category. This is because they consider that currently sufficient funding in the village is available, mainly sourced from DD and ADD; second, the level of government participation is classified as â€œstrongâ€ and â€œvery strongâ€. This means that indicators such as the preparation of regulations, government involvement in program preparation, assistance in the implementation of development, evaluation regarding the use of DD and ADD, and utilization of development results are as expected. However, indicators such as the extent to which the government's ability to open access to cooperation with investors in managing potential in the village still needs to be improved or in the â€œsufficientâ€ category; and third, the level of private sector participation is generally classified as â€œweakâ€ and â€œsufficientâ€. Starting from the planning stage to the utilization of the results of the private sector participation level, it still needs to be improved. Respondents assessed that the impact of the available CSR has not been felt at the village level.